Association Between Breakfast Consumption and Anthropometrically Determined Nutritional Status of Secondary-School Adolescents in Lagos, Southwest Nigeria - Foluke Adenike Olatona; Oyetola Oloruntola; Oluwafunmilayo Adeniyi; Eyitope Amu (International Journal of Maternal and Child Health and AIDS, 2022)
Background and Objectives: Breakfast skipping has been associated with obesity among adolescents in some studies but little is known about the relationship between breakfast consumption and obesity among secondary-school adolescents in Nigeria. This study contributes to the empirical literature by analyzing the relationship between breakfast consumption and anthropometrically determined nutritional status of secondary-school adolescents in Lagos, Nigeria.